2021
DOI: 10.1021/acs.est.1c03913
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Modeling and Apportionment of Diesel-Related Contributions to Black Carbon Concentrations

Abstract: Exposure to diesel-related air pollution, which includes black carbon (BC) as a major component of the particulate matter emitted in engine exhaust, is a known human health hazard. The resulting health burden falls heavily on vulnerable communities located close to major sources including highways, rail yards, and ports. Determination of source contributions to the overall pollution burden is challenging due to collinearity in the exhaust composition profiles for relevant sources including heavy-duty diesel tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The community is surrounded by freeways and is burdened with exposure to diesel exhaust coming from many sources, including heavy-duty trucks, locomotives, marine vessels, and cargo-handling equipment. Previous modeling work focused on this area has shown that even relatively high spatial resolution (150 m) is not fine enough to resolve elevated BC concentrations near sources …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The community is surrounded by freeways and is burdened with exposure to diesel exhaust coming from many sources, including heavy-duty trucks, locomotives, marine vessels, and cargo-handling equipment. Previous modeling work focused on this area has shown that even relatively high spatial resolution (150 m) is not fine enough to resolve elevated BC concentrations near sources …”
Section: Methodsmentioning
confidence: 99%
“…WRF is a numerical weather prediction model that can simultaneously model meteorology and tracer species, allowing for complete online coupling of the meteorological modeling and tracer transport. The model set-up was similar to that used in previous work by Hamilton and Harley, 42 with three one-way nested domains and horizontal grid resolutions of 4.05 km, 1.35 km, and 150 m, with an additional fourth nest at 50 m horizontal resolution as shown in Figure 1. The nesting configuration allows BC to be transported from parent to child domains, so for example, BC emitted in San Francisco (west, and typically upwind of West Oakland) will be accounted for in total modeled concentrations within the smallest 50 m domain.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations